2019
DOI: 10.1177/0731948719892021
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Interventions for Students With Learning Disabilities: A Research Synthesis

Abstract: The purpose of this study was to examine geometry interventions for students with learning disabilities. We synthesized nine intervention studies by focusing on the geometry concepts and skills taught to students with learning disabilities, intervention types used, instructional components embedded, and the methodological rigor of the studies. Intervention studies were mainly single-case designs. The geometry topics included angle recognition, and perimeter, area, and volume problems. The findings of this synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The implication for teachers is that they should be aware that the materials they choose will influence how children think about the mathematics targeted by those materials. Consistent with the findings of two studies recently published in this journal ( Doabler et al, 2020 ; Liu et al, 2020 ), our results provide a potentially important instructional consideration: The use of materials will shape children’s thinking about numeration and should be taken into account in the future design of high-quality interventions with at-risk children.…”
Section: Discussionsupporting
confidence: 89%
“…The implication for teachers is that they should be aware that the materials they choose will influence how children think about the mathematics targeted by those materials. Consistent with the findings of two studies recently published in this journal ( Doabler et al, 2020 ; Liu et al, 2020 ), our results provide a potentially important instructional consideration: The use of materials will shape children’s thinking about numeration and should be taken into account in the future design of high-quality interventions with at-risk children.…”
Section: Discussionsupporting
confidence: 89%
“…Efforts have also been made to bring together information deriving from the most specific research in the form of various synthesis studies, meta-analyses and systematic literature reviews. We found fewer synthesis studies, and most of them targeted learning disabilities (e.g., Liu et al, 2021;McKenna et al, 2015;Ok et al, 2020) or some other narrow area compared with our own research (e.g., Abdulrahim & Orosco, 2020;Eames et al, 2021). For example, Abdulrahim and Orosco (2020) targeted the teaching of mathematics to linguistically diverse learners, whereas Eames et al (2021) focused on learning about function as a concept.…”
mentioning
confidence: 65%
“…Less than half of the time, studies reported the math content and activities used in the comparison condition, as well as the instructional time and nature of instruction in the comparison. Previous researchers have noted similar limitations of reporting fidelity of implementation (Jitendra et al, 2016;Liu et al, 2019). Providing researchers with information about the comparison condition is important in intervention research (including in meta-analyses of interventions) because the magnitude of intervention effects may be influenced by what instruction is provided in the comparison condition.…”
Section: Quality Of Reporting Intervention and Comparison Conditionsmentioning
confidence: 99%
“…Previous researchers have examined study quality in school-based math intervention meta-analyses. The studies reported varying results, with average study reporting quality ratings (scale of 0 to 1) ranging from, for example, 0.77 for geometry interventions for 4 th - to 12 th -grade students with learning disabilities (Liu et al, 2019) to 0.83 for tier 2 math interventions for students with math difficulty (Jitendra et al, 2021) to 0.87 for proportional reasoning interventions for students with math difficulty (Nelson, Hunt, et al, 2022). Wide ranges in study reporting quality across math interventions within the same meta-analysis have been documented (e.g., Stevens et al, 2018).…”
Section: Study Reporting Qualitymentioning
confidence: 99%